2002
DOI: 10.1055/s-0037-1613017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Coagulation Test Abnormalities to Tumour Burden and Postoperative DVT in Resected Colorectal Cancer

Abstract: SummaryIn a prospective study, coagulation test results were compared in 137 patients with colorectal cancer (CRC) and 39 subjects with benign colorectal diseases. Prothrombin fragment 1+2 (F1+2), thrombinantithrombin complex (TAT), and soluble fibrin (SF) were measured in plasma before and after surgery. CRC patients presented with significantly higher values of F1+2 and TAT than controls. Patients with localised CRC had elevated values of F1+2 and TAT, whereas patients with advanced CRC also had elevated SF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…2). Of these, 11 studies reported data on F1.2 15,19,[25][26][27][28][29][30][31][32][33] (►Table 2), nine studies reported data on TAT [25][26][27]30,[33][34][35][36][37] (►Table 3), and 12 studies reported data Embase ('malignant neoplasm'/exp OR cancer à OR neoplasm à OR malignanc à ) AND ('thromboembolism'/exp OR "venous thromboembolism" OR "venous thrombo-embolism" OR "venous thrombosis" OR "deep vein thromboembolism" OR "deep vein thrombosis" OR "portal thrombosis" OR "sinus thrombosis" OR "mesenterial thrombosis" OR "cerebral vein thrombosis" OR "cancer-associated thrombosis" OR "VTE" OR "DVT") AND ('thrombin'/exp OR 'thrombography'/exp OR "thrombin" OR "calibrated automated thrombogram" OR "thrombography" OR "prothrombin" OR 'thrombin antithrombin complex'/exp OR "TAT" OR "thrombinantithrombin") NOT 'conference abstract'/it on thrombin generation 13,21,28,29,31,[38][39][40][41][42][43][44] (►Table 4). Of the 24 included papers, 13 were rated as good, eight as fair, and three studies were rated as poor.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2). Of these, 11 studies reported data on F1.2 15,19,[25][26][27][28][29][30][31][32][33] (►Table 2), nine studies reported data on TAT [25][26][27]30,[33][34][35][36][37] (►Table 3), and 12 studies reported data Embase ('malignant neoplasm'/exp OR cancer à OR neoplasm à OR malignanc à ) AND ('thromboembolism'/exp OR "venous thromboembolism" OR "venous thrombo-embolism" OR "venous thrombosis" OR "deep vein thromboembolism" OR "deep vein thrombosis" OR "portal thrombosis" OR "sinus thrombosis" OR "mesenterial thrombosis" OR "cerebral vein thrombosis" OR "cancer-associated thrombosis" OR "VTE" OR "DVT") AND ('thrombin'/exp OR 'thrombography'/exp OR "thrombin" OR "calibrated automated thrombogram" OR "thrombography" OR "prothrombin" OR 'thrombin antithrombin complex'/exp OR "TAT" OR "thrombinantithrombin") NOT 'conference abstract'/it on thrombin generation 13,21,28,29,31,[38][39][40][41][42][43][44] (►Table 4). Of the 24 included papers, 13 were rated as good, eight as fair, and three studies were rated as poor.…”
Section: Resultsmentioning
confidence: 99%
“…Some variability in sample processing and analysis between studies was noted. For instance, Leiba et al 41 used a shorter centrifugation time, and Iversen et al 26,27 and Kirwan et al 34 utilized cooled centrifugation, which may impact results. However, the number of commercially available assays are limited, and the analysis principles are largely similar within the three analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations